2016
DOI: 10.1177/1526924816655266
|View full text |Cite
|
Sign up to set email alerts
|

Organ Procurement in Forensic Deaths

Abstract: The need for organs has increased in the recent years, and this shortage will only worsen. In addition to the organs procured from brain-dead donors, a procedure for non-heart-beating donors was therefore developed. When deaths involve legal proceedings, the medical examiner makes the decision of whether or not to remove organs. To assist medical examiner in their decision-making, a number of forensic scientific societies aimed to develop recommendations, and legal adjustments were adopted. Nevertheless, these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
(34 reference statements)
1
2
0
Order By: Relevance
“…Traumatised bodies that could constitute evidence are not taken because they have no therapeutic value. Our study also showed, as have many works published in the literature, [17][18][19][20][21] that if strict rules are observed and if a pathologist can examine the donor's body, there should be little or no doubt about any forensic conclusions: of the 27 autopsies performed after organ procurement that were analysed in this study 15 (eight criminal, eight suicidal, nine accidental, two medical malpractice), none showed interpretation bias related to surgical procedures, if procedural and scientific rigour in this process was followed to ensure judges the preservation of evidence.…”
Section: Creation Of a Scientific Protocol By The French Society Of Fsupporting
confidence: 76%
See 1 more Smart Citation
“…Traumatised bodies that could constitute evidence are not taken because they have no therapeutic value. Our study also showed, as have many works published in the literature, [17][18][19][20][21] that if strict rules are observed and if a pathologist can examine the donor's body, there should be little or no doubt about any forensic conclusions: of the 27 autopsies performed after organ procurement that were analysed in this study 15 (eight criminal, eight suicidal, nine accidental, two medical malpractice), none showed interpretation bias related to surgical procedures, if procedural and scientific rigour in this process was followed to ensure judges the preservation of evidence.…”
Section: Creation Of a Scientific Protocol By The French Society Of Fsupporting
confidence: 76%
“…In a previous study conducted at our institution between 2003 and 2011, 15 we noted that the main reasons given by judges for opposing organ removal in legal situations were lack of information on the circumstances of death (17%), the criminal nature of the death (28%) and, most importantly, the need for an autopsy (38%). This last and most-often expressed reason for opposition to judicial organ harvesting suggests that judges consider that autopsy findings may be hampered by the organ removal because of the required surgical procedures.…”
Section: Harvesting and Forensic Deathsmentioning
confidence: 99%
“…Again, the conflict of procuring organs for cadaveric organ donations collides with criminal investigations, which needed efforts both from scientific and procedural rigour as well as the judicial policy of zero refusals to harmonize the two conflicting needs). 27 An interesting report emerged from Spain where excellent coordination between a forensic institute, local judicial system, and local tissue bank has demonstrated that seamless interaction between related agencies can provide a win-win situation in the battle of requiring forensic outcomes versus making full use of cadaveric organ donations. Albeit the donated organ, in this case, is mainly the cornea, it still offers hope and directional policy to cater to both needs.…”
Section: Non-maleficencementioning
confidence: 99%